The importance of riparian vegetation in maintaining spring water quality in Yeh Penet Watershed, Bali, Indonesia - FEBRI ARIF CAHYO WIBOWO; ARISKA DWI PRAMUDYA ARISKA DWI PRAMUDYA; TATAG MUTTAQIN; MOCHAMMAD NICKO AGUNG PANGESTU (Society for Indonesian Biodiversity, 2024)
Abstract. Wibowo FAC, Pramudya AD, Muttaqin T, Pangestu MNA. 2024. The importance of riparian vegetation in maintaining spring water quality in Yeh Penet watershed, Bali, Indonesia. Biodiversitas 25: 2051-2062. Water quality changes along with population growth and human activities. Riparian ecosystems play an important role in maintaining water quality since riparian vegetation have a complex root system which acts as a filter of toxic substances to not enter the spring water. This research analyzes the relationship between riparian vegetation and water quality at five springs in the bamboo rehabilitation area of the Environment Bamboo Foundation (YBLL) in the Yeh Penet Watershed, Bali, Indonesia. At each spring, vegetation analysis was carried out to determine the diversity and composition of riparian vegetation, as well as water quality assessment based on bio-physiochemical parameters. The result of vegetation analysis found that spring 1 was dominated by Equisetum hyemale, spring 2 by Diplazium esculentum, spring 3 by Digitaria longiflora and springs 4 and 5 by Musa paradisiaca. The analysis of bio-physicochemical parameters showed that the water from the five springs was suitable for consumption, but it needs to be heated to a temperature of ±100°C before consuming it due to the presence of coli bacteria. Riparian vegetation diversity had a strong relationship with water quality parameters especially Biochemical Oxygen Demand (BOD) values, Ammonia (NH3), and total coliform. Our findings confirm the importance of riparian vegetation in maintaining water quality in water springs within a watershed.